Completeness Correlation Of Medical Resumes Inpatients Toward Continuity Claims BPJS At The Qadr Tangerang Hospital - Tri Harti Maya Utami; Lily Widjaja (Lembaga Penerbitan Universitas Esa Unggul, 2016)
AbstractCompleteness of medical resumes are things that need to be considered, because it plays an important role in ensuring the continuity of medical services and is the main requirement in filing claims in hospitals, health centers and all healthcare providers (PPK) to the Security Agency of Health (BPJS), all components of the resume medical needs include medical and resumes must be timely so that the claims process runs smoothly. Incomplete medical resume can lead to rejection by the verification BPJS so the claim file must be returned to the hospital in order to be completed. Thus the process of filing a claim to BPJS become obstructed and the claims process can not run smoothly. This resulted in delays in the disbursement of BPJS that can affect cash flow thus hampering the operations Hospital Hospital services such as late payment for services provided, the purchase of facilities and infrastructures that support services in house Sakit.Untuk determine the relationship completeness of medical inpatients resume to smoothness claims to BPJS Hospital Tangerang. The Research Qadr hospital was quantitative research, conducted by observation, look for the relationships between independent variables and the dependent variable is the completeness of medical inpatients resume the smooth claims to BPJS.Pengambilan samples using systematic random sampling of population 528 medical patients resume BPJS Hospitalization in April 2016 and samples taken 50 resumes medical research, data analysis using Chi-square test. Of the four components of the overall amount of the recapitulation completeness complete an average of 43 (86%) and incomplete 7 (26%). Claims BPJS fluent 31 (62%) and non-current 19 (38%). Chi-square test results. obtained P-value 0.000 <0.05 then Ho is rejected or there is a relationship between the completeness of medical resumes with the smoothness of a claim to BPJS Qadr Hospital in Tangerang. OR = 540 (95% CI: 31.7 - 9175), means completeness resume full medical have the opportunity smoothness of claims amounting to 540 times compared to the completeness of the medical resumes incomplete, and in research iniditeltiti also code for accuracy of diagnosis as a variable comparator (counfounding) and obtained 0. the results of P-value 0.000 <0.05 then Ho is rejected, so it can be concluded that there is a relationship between the accuracy of diagnosis by the smooth code claims to BPJS Qadr Hospital in Tangerang. Values obtained 31 OR (95% CI: 5.5 to 177), meaning that accuracy appropriate diagnosis code has a chance to claim fluency by 31 times compared to the accuracy of diagnosis codes that are not appropriate. it can be concluded that both these factors affect each other klaim.Therefore, it is expected the doctor fills the resume completely and correctly in order to reach the level of completeness of the standard 100% and do coding by following the procedures for book-coding based on the theory that ICD-10 volume 2 in order to meet the performance standards coding accuracy> 84%, as well as medical records clerk needs to perform quantitative and qualitative analysis.Keywords: Completeness of medical resumes, diagnosis code accuracy, fluency claims. AbstrakKelengkapan resume medis merupakan hal yang perlu diperhatikan, karena berperan penting dalam menjamin kontinuitas pelayanan medis dan merupakan syarat utama dalam pengajuan klaim di Rumah Sakit, Puskesmas dan semua penyedia pelayanan kesehatan (PPK) ke Badan Penyelenggara Jaminan Kesehatan (BPJS), semua komponen pada resume medis perlu dilengkapi dan resume medis harus tepat waktu agar proses klaim berjalan dengan lancar. Ketidaklengkapan resume medis dapat menyebabkan penolakan oleh verifikator BPJS sehingga berkas klaim harus dikembalikan kepada Rumah Sakit agar segera dilengkapi. Dengan demikian proses pengajuan klaim ke BPJS menjadi terhambat dan proses klaim tidak dapat berjalan lancar. Hal ini berdampak pada keterlambatan pencairan dana dari BPJS yang dapat mempengaruhi cash flow Rumah Sakit sehingga menghambat operasional RS seperti keterlambatan pembayaran jasa atas pelayanan yang diberikan, pembelian sarana dan prasaran yang menunjang pelayanan di Rumah Sakit.Untuk mengetahui hubungan kelengkapan resume medis pasien rawat inap terhadap kelancaran klaim ke BPJS di Rumah Sakit Qadr Tangerang.Penelitian ini merupakan penelitian kuantitatif,dilaksanakan dengan observasi,dicari hubungan atau keterkaitan antara variabel independen dan variabel dependen yaitu Kelengkapan resume medis pasien rawat inap terhadap kelancaran klaim ke BPJS.Pengambilan sampel menggunakan systematic random sampling dari populasi 528 resume medis pasien BPJS Rawat Inap bulan April 2016 dan diambil sampel penelitian 50 resume medis, analisis data menggunakan uji Chi-square. Dari 4 komponen jumlah jumlah hasil rekapitulasi kelengkapan keseluruhan yang lengkap rata-rata 43(86%) dan tidak lengkap 7(26%).Klaim BPJS yang lancar 31(62%) dan yang tidak lancar 19(38%). Hasil uji Chi-square. didapatkan P-value 0.000 < 0,05 maka Ho ditolak atau ada hubungan antara kelengkapan resume medis dengan kelancaran klaim ke BPJS di Rumah Sakit Qadr Tangerang. OR= 540 (95%CI: 31.7 – 9175), artinya kelengkapan resume medis yang lengkap mempunyai peluang kelancaran klaim sebesar 540 kali dibanding kelengkapan resume medis yang tidak lengkap, dan dalam penelitian ini diteltiti juga ketepatan kode diagnosa sebagai variabel pembanding (counfounding) dan didapatkan hasil P-value 0. 0.000 < 0.05 maka Ho ditolak, sehingga dapat disimpulkan bahwa ada hubungan antara ketepatan kode diagnosa dengan kelancaran klaim ke BPJS di Rumah Sakit Qadr Tangerang. Nilai OR yang diperoleh 31 (95%CI: 5,5 – 177), artinya ketepatan kode diagnosa yang tepat mempunyai peluang kelancaran klaim sebesar 31 kali dibanding ketepatan kode diagnosa yang tidak tepat. maka dapat disimpulkan bahwa kedua faktor tersebut saling mempengaruhi kelancaran klaim.Oleh karena itu, diharapkan dokter mengisi resume dengan lengkap dan benar agar tingkat kelengkapan mencapai standar 100% dan melakukan pengodean dengan mengikuti tata cara pengodean berdasarkan teori yaitu buku ICD-10 volume 2 agar dapat memenuhi standar kinerja ketepatan pengodean > 84%, serta petugas rekam medis perlu melakukan analisis kuantitatif dan kualitatif.Kata kunci : Kelengkapan resume medis, ketepatan kode diagnosa, kelancaran klaim.